Penerapan Metode Simpel Moving Average Untuk Memprediksi Persediaan Tiket Kapal Di Pelabuhan Penyeberangan Gorontalo: Stock up on boat tickets at the Gorontalo crossing port - Nuraini Azis; Muis Nanja; Zohrahayaty (Teknik Informatika Fakultas Ilmu Komputer Universitas Ichsan Gorontalo, 2023)
Transportation is one of the basic needs of society, both by air, land and sea. Sea shipping at the Gorontalo Ferry Port is the main means of advancing the national economy. Many people choose executive boats to travel because they are fast, comfortable and safe. Before traveling, prospective passengers on executive ships must first book tickets with an agent who determines where they will go and when the ship will depart [2]. Tickets are tools/media that are used by certain companies as a direct substitute for gold. Tickets are usually in the form of paper containing certain items that show value. According to the Big Indonesian Dictionary, ticket